Preliminary evaluation methodology for payback infrastructure projects in private-public partnership - Shergin, D. A.; Annenkov, G. A. (Finansy: teoriâ i praktika (Online), 2023)
The authors of the article present the results of scientific and practical research on the development of methods of primary assessment of the efficiency of payback infrastructure projects public-private partnerships achieved through the monitoring and analysis of the state company’s investment activities and project portfolio management. The purpose of this study is to develop methodology for preliminary evaluation of payback infrastructure projects, that is able to be used to evaluate efficiency of capital investment at the stage of initial project appraisal and planning and to range perspective projects in accordance with their efficiency. The subject of the article: efficiency of payback investment projects in the infrastructure industry. The relevance of the study is determined by absence of a generally accepted methodology for initial evaluation of investment projects, that allows for into consideration the legal and economic specifics of federal projects approval and implementation in the regions of Russia. The methodology formed on the basis of an interdisciplinary approach implemented in the course of approval and evaluation practice of investment projects appraisal within the framework of the activities of a state-owned company. The instrumentation reviewed in this paper is based on data from financial modeling of infrastructure projects, with preliminary geographical modeling of traffic flow intensity. It includes the following modified indicators based on discounted cash flows: consolidated coverage ratio, ratio of operating income to capital investment, share of extrabudgetary funding in the life cycle of a project, internal rate of return. These indicators are unified into a single integral indicator, which allows to rank and manage future projects in a company’s portfolio. The applicability of the proposed methodology has been verified by the results of implementation of the public-private partnership projects. Based on the results of the study a financial model for initial assessment of project efficiency has been prepared, which can be used as the initial stage of project justification.